Developing a Calorie Requirement Application Based on a BMI Calculator for Android Using User-Centered Design (UCD) - Fadjri Astra Ryan Sinurat; Heny Pratiwi; Ahmad Fajri (Poltanesa, 2025)
This study aims to develop an Android-based calorie requirement application using the User-Centered Design (UCD) approach and to evaluate its usability through the System Usability Scale (SUS). The application calculates individualized calorie needs using the Basal Metabolic Rate (BMR) and Total Daily Energy Expenditure (TDEE) formulas, while the Body Mass Index (BMI) feature functions only as a weight classification tool to support user awareness. Healthcare workers at Puskesmas Loa Ipuh were involved throughout the research, concept development, design, prototyping, and testing stages to ensure that the system aligns with real user needs. The UCD process used in this study consists of five stages: research, concept, design, development, and testing. The final application was built using the Kotlin in Android Studio and includes features such as calorie calculation, BMI calorie calculates, food recommendations, and daily nutritional tracking. Usability evaluation with the System Usability Scale involved 23 respondents and resulted in an average score of 82.60, which falls into the “excellent” category, indicating that the application is easy to use, efficient, and well accepted by target users. These findings demonstrate that integrating UCD with validated calorie estimation formulas can produce a functional and user-centered mobile application that supports users in understanding their daily calorie needs and improves accessibility to basic nutritional information.